Pemberian Yoghurt Pala Efektif untuk Menurunkan Kadar Kolesterol Serum Darah Tikus Model Hiperkolesterolemia - Unitly, Adrien Jems Akiles; Moniharapon, Debby D.; Baszary, Chomsa Dintasari Umi; Sikafir, Beatrix Belina; Silahooy, Veince B.; Watuguly, Theopilus Wilhelmus; Seimahuira, Theresia Natalia; Lesbatta, Kezia Josawel; Sillehu, Eka Safitri; Ratulewen, Desi Ellida; Raprap, Roswanti T. (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Hypercholesterolemia can cause metabolic disorders. Yogurt and nutmeg have the potential to lower blood cholesterol levels that exceed normal levels. The purpose of this study was to analyze the effect of nutmeg yogurt administration to reduce blood serum cholesterol levels in hypercholesterolemia model rats. This study applied a completely randomized design using 15 Rattus norvegicus Sprague-Dawley varieties with a body weight of 200g per rat, which were divided into five treatments and three replications, namely negative control (normal diet, without fat induction/nutmeg yogurt for 14 days), positive control (fat diet 2 ml/rat/day + simvastatin 1 ml/rat/day for 14 days), treatment 1 (fat diet 2 ml/rat/day + nutmeg yogurt 1.25 ml/rat/day for 14 days), treatment 2 (fat diet 2 ml/rat/day + nutmeg yogurt 2.5 ml/rat/day for 14 days), and treatment 3 (fat diet 2 ml/rat/day + nutmeg yogurt 5 ml/rat/day for 14 days). Blood cholesterol levels were measured in all groups, and the results were compared using an ANOVA test. The results showed that administration of nutmeg yogurt can lower blood cholesterol levels, with an effective dose of 2.5 ml. The mechanism of action of nutmeg yogurt in lowering cholesterol levels is by competitively inhibiting the enzyme 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase, inhibiting the activity of the HMG-CoA reductase enzyme that converts acetyl-CoA to mevalonic acid, the initial step in the cholesterol biosynthesis pathway, thus inhibiting cholesterol formation. Furthermore, it was concluded that nutmeg yogurt at a dose of 2.5 ml/rat/day was effective as an antihypercholesterolemic agent in rats, potentially serving as an adjuvant therapy.Keywords: hypercholesterolemia; nutmeg; yogurt